PENGGUNAAN BAHASA INDONESIA DALAM KARYA ILMIAH GURU SMP DI KABUPATEN PIDIE JAYA - Rahmi, Hayatun; S, Nofiana (Jurnal Sains Riset, 2022)
This research is entitled The Use of Indonesian in Scientific Work of Middle School Teachers in Pidie Jaya Regency. The formulation of the problem in this study is "How is the use of Indonesian in scientific work for junior high school teachers in Pidie Jaya Regency?". Based on the formulation of the problem, the purpose of this study is to describe the use of Indonesian in the scientific work of junior high school teachers in Pidie Jaya district. The approach used in this research is a qualitative approach with descriptive analysis type of research. Researchers used reading and note-taking techniques. This is based on the consideration that this technique is considered the most appropriate for the data source, namely the scientific work of a junior high school Indonesian language teacher. Data collection techniques using reading and note-taking techniques. The data analysis techniques used in this study are (1) Data Collection, (2) Data Reduction, (3) Data display, (4) Conclusion drawing and verification. The research shows that the data examined in 6 scientific works of teachers in Pidie Jaya district there are 44 errors in the use of standard language consisting of 7 types of errors, namely, errors that are influenced by the regional language there are 2 errors or (4.44%), influenced by foreign terms there are 6 (13.63%) errors, there were 3 (6.81%) errors in the variety of spoken language, 20 (45.45%) errors in the use of diction, 1 (2.27%) ambiguity, 10 (22.72%) errors in pleonasm, and 2 hypercorrections ( 4.54%) errors So, the most common errors found in this study were diction errors, namely 20 (45.44%) errors, and the error that I got the least was ambiguous error 1 (2.27%).Keywords: Indonesian, teacher's scientific work